Spirulina supplementation in a mouse model of diet-induced liver fibrosis reduced the pro-inflammatory response of splenocytes. Issue 7 (26th February 2019) - Pham, Tho X.; Lee, Yoojin; Bae, Minkyung; Hu, Siqi; Kang, Hyunju; Kim, Mi-Bo; Park, Young-Ki; Lee, Ji-Young
Abstract: Treatment of liver fibrosis is very limited as there is currently no effective anti-fibrotic therapy. Spirulina platensis (SP) is a blue-green alga that is widely supplemented in healthy foods. The objective of this study was to determine whether SP supplementation can prevent obesity-induced liver fibrosis in vivo . Male C57BL/6J mice were randomly assigned to a low-fat or a high-fat (HF)/high-sucrose/high-cholesterol diet or an HF diet supplemented with 2·5 % SP (w/w) (HF/SP) for 16 or 20 weeks. There were no significant differences in body weight, activity, energy expenditure, serum lipids or glucose tolerance between mice on HF and HF/SP diets. However, plasma alanine aminotransferase level was significantly reduced by SP at 16 weeks. Expression of fibrotic markers and trichrome stains showed no differences between HF and HF/SP. Splenocytes isolated from HF/SP fed mice had lower inflammatory gene expression and cytokine secretion compared with splenocytes from HF-fed mice. SP supplementation did not attenuate HF-induced liver fibrosis. However, the expression and secretion of inflammatory genes in splenocytes were significantly reduced by SP supplementation, demonstrating the anti-inflammatory effects of SP in vivo . Although SP did not show appreciable effect on the prevention of liver fibrosis in this mouse model, it may be beneficial for other inflammatory conditions.